Effect of irradiated protein sources, fed in meal or pelleted diets, on nursery pig performance - C N Groesbeck; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2006)
A total of 350 pigs (initially 10.8 ± 2.1 lb and 21 ± 3 d of age) were used in a 22-d trial to determine the effects of feeding irradiated protein sources (spray-dried animal plasma, soybean meal, fish meal, or all three), in meal and pelleted diets, on the growth performance of nursery pigs. Pigs were blocked by weight, with 5 pigs/pen and 7 pens/treatment. From d 0 to 11, pigs were fed 1 of 10 experimental treatments, which consisted of the same diet fed in either meal or pelleted form, containing either no irradiated protein sources or containing irradiated spray-dried animal plasma, soybean meal, fish meal, or all three irradiated protein sources; then all pigs were fed a common diet (meal form) from d 11 to 22. Irradiation of the protein sources, as well as pelleting, reduced total bacterial and coliform counts. There were no irradiation by diet form interactions (P>0.16) observed for growth performance. From d 0 to 11, there was no irradiation effect (P>0.16) of protein source on ADG, ADFI, or F/G. But pigs fed pelleted diets had improved (P<0.02) F/G, compared with pigs fed meal diets, with no difference in ADG and ADFI. From d 11 to 22, pigs previously fed meal diets had a tendency for improved (P<0.10) ADFI, compared with that of the pigs fed pelleted diets. Overall (d 0 to 22), pigs fed diets containing irradiated protein sources had a tendency for improved (P<0.13)F/G, compared with that of pigs fed control diets. Pigs fed meal diets had a tendency for improved (P<0.12) ADFI, compared with the ADFI of pigs fed pelleted diets. Pigs fed pelleted diets had improved (P<0.01) F/G, compared with that of pigs fed meal diets. These data confirm that irradiation of protein ingredients, as well as pelleting, will reduce total bacteria and coliform counts within individual feed ingredients or a complete diet. Although irradiation of protein source did not improve performance in this study, pelleting of diets improved feed efficiency.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Nursery pig; Pellet; Protein source; Irradiation; Swine